Integrasi Model Pembelajaran Holistik Untuk Optimalisasi Perkembangan Kognitif Anak Usia Dini - Sri Jumiaty Permatasari; Itsnain Alfajri Husain; Chairan Zibar L. Parisu (Journal of Humanities, Social Sciences, and Education, 2025)
Early childhood cognitive development is an important foundation in forming thinking skills, problem solving, and lifelong learning. The holistic learning model is seen as an approach that is able to integrate various aspects of child development, including cognitive, emotional, social, and physical simultaneously. This article is a literature study that aims to analyze the integration of holistic learning models in order to optimize the cognitive development of early childhood. By reviewing various current scientific sources, it was found that the holistic model encourages children to learn through direct experience, active play, and positive emotional involvement. This model places children as active subjects in the learning process, thus providing space for the emergence of initiative, exploration, and reflection. This study concludes that the implementation of holistic learning, such as the Reggio Emilia, Montessori, and HighScope approaches, has been proven to be able to strengthen children's critical thinking processes, memory abilities, and logic skills. This study recommends the need for ongoing training for PAUD educators to be able to integrate holistic principles in the planning and implementation of learning.